Is fetal magnetic resonance imaging indicated in patients with isolated ventriculomegaly?. (September 2019) - Doğan Durdağ, Gülşen; Yılmaz Baran, Şafak; Kalaycı, Hakan; Alkan, Özlem
Abstract: Objective: Ventriculomegaly is one of the most common anomalies encountered at obstetric ultrasound and it necessitates follow up. Fetal magnetic resonance imaging (MRI) can be used to confirm the ultrasound diagnose or to detect additional anomalies. Aim of this study is to assess follow up and management of fetal ventriculomegaly shown by ultrasound, and to evaluate additional diagnostic contribution of MRI. Study Design: This study was conducted retrospectively including 89 patients who had fetal MRI subsequent to ultrasound diagnose of ventriculomegaly in between 2011-2017. Medical records of patients were investigated and accompanying anomalies, congenital infection, chromosomal examination, degree and progression of ventriculomegaly, neonatal imaging and diagnose, and neurodevelopmental findings on follow up were evaluated. Patients were classified in two groups as isolated and nonisolated ventriculomegaly, and subgroups mild, moderate, severe were formed according to their findings. SPSS 23.0 programme was used for statistical analysis. Results: Ultrasound and following MRI was performed in a range of 18-35 th gestational weeks, diagnoses were isolated ventriculomegaly for 56 patients and nonisolated ventriculomegaly for 33 patients. Progression and neurodevelopmental delay was higher in severe nonisolated ventriculomegaly group. There was not significant contribution of MRI in the follow up of isolated ventriculomegaly (p < 0.001), and diagnostic imaging findings declined in neonatal period with proceeding normal neurodevelopment in 92.7% of patients followed with diagnosis of isolated ventriculomegaly. Conclusion: When isolated ventriculomegaly is detected, ultrasound performed by an experienced team is mostly sufficient. MRI can be used in suspicious cases or when ventriculomegaly progresses.